THE EFFECT OF COMPENSATION AND WORKLOAD ON JOB SATISFACTION OF TEACHERS AT STATE SENIOR HIGH SCHOOL 1 TAKALAR - Sayba, Sayba; Kurniawan, Agung Widhi; Ruma, Zainal; Burhanuddin, Burhanuddin; Abadi, Rahmat Riwayat (Universitas Negeri Makassar, 2026)
Abstract: This study aims to determine and analyze the effect of financial compensation, non-financial compensation, and workload on job satisfaction of teachers at SMA Negeri 1 Takalar. This study uses a quantitative approach with a descriptive method. The study population was all 76 teachers who were also respondents through a saturated sampling technique. Data collection was carried out through distributing questionnaires and interviews, then analyzed using multiple linear regression with the help of the SPSS version 25 application. The results of the study indicate that financial compensation, non-financial compensation, and workload partially or simultaneously do not have a significant effect on teacher job satisfaction. This indicates that other factors outside this study are likely more dominant in influencing teacher job satisfaction, such as the work environment, leadership, and intrinsic motivation.Keywords: Compensation, Workload, Job Satisfaction